how do you solve?

Assume the student meant 1/(x^{2}-4) = 6/x

Cross multiplication leads to x = 6x^{2} - 24

Collect all terms in one side,

6x^{2} - x - 24 = 0

Apply quadratic formula,

x = (1/12)[1 +/- sqrt(577)]

how do you solve?

Tutors, sign in to answer this question.

Assume the student meant 1/(x^{2}-4) = 6/x

Cross multiplication leads to x = 6x^{2} - 24

Collect all terms in one side,

6x^{2} - x - 24 = 0

Apply quadratic formula,

x = (1/12)[1 +/- sqrt(577)]

You can either start by multiplying both sides of the equation by x^{2}, or rearrange it this way (both get the same result):

1/x^{2} - 4 = 6/x ====> 1/x^{2} = 6/x + 4 and now multiply both sides by x^{2}

x^{2}*1/x^{2} = 6x^{2}/x + 4x^{2 } =====> 1 = 6x + 4x^{2
}=====> 0 = 4x^{2} + 6x -1

Now it's in the form ax^{2} + bx + c you can use the quadratic formula to find x:

x = [-b ± √(b^{2} - 4ac)]/(2a)

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.